Probing the Martensitic Microstructure of Magnetocaloric Heusler Films by Synchrotron Diffraction. Issue 8 (18th July 2018) - Schwabe, Stefan; Schleicher, Benjamin; Niemann, Robert; Hühne, Ruben; Walter, Peter; Nielsch, Kornelius; Waske, Anja; Fähler, Sebastian
Abstract: First‐order, magnetocaloric materials are promising for energy efficient solid‐state cooling because of their high entropy changes, but they have the drawback of a hysteresis due to the nucleation and growth of the involved phases. Here, synchrotron based X‐ray diffraction is used to investigate epitaxial Ni−Mn−Ga−Co thin films grown on Pb(Mg1/3 Nb2/3 )0.72 Ti0.28 O3 (PMN‐PT). This integral method is used to test several hypotheses regarding structure and orientation of the martensite, whose nucleation was proposed to be the decisive contribution to hysteresis in Heusler materials. The measurements are compared to a recently proposed model of the martensitic nuclei, combining the phenomenological martensite theory with the adaptive concept. This investigation demonstrates that the diffraction patterns are consistent with a martensitic nucleus built from 8 variants forming a ‐ b laminates. Additionally, it is shown that in accordance with the surface morphology of these films only a subset of nuclei occur, namely those needed to form type X martensite. Abstract : Surface morphology and diffraction pattern of magnetocaloric Heusler films exhibit X‐like features. Both features in real and reciprocal space can be described by one single parameter and by considering the reduced symmetry of thin films compared to bulk. With this, four hypotheses on the nucleation of martensite, which is responsible for hysteresis losses occurring in the material, are confirmed.